Adaptive Coordinated Reception for Multicell MIMO Uplink. (27th January 2011) - Lu Lu, Xiaojia Xiaojia; Li Li, Wei Wei; Tölli Tölli, Antti Antti; Juntti Juntti, Markku Markku
Abstract : We study the coordinated reception amongst multiple base stations (BS) in the uplink cellular system, where each mobile station (MS) is served by an associated multiple BS set (MBS). Under the individual signal-to-interference-plus-noise ratio (SINR) constraint per MS, power control and receive beamforming are jointly optimized with adaptive MBS selection to minimize the total transmit power. An iterative optimization algorithm is presented accordingly. The joint optimization problem is nonconvex in general, but it can be optimally solved by the proposed algorithm as long as it is feasible. To find the optimum, the proposed algorithm requires the exhaustive search over all BSs per MS. To reduce the complexity in the large-scale cellular network, we propose simplified schemes where a subset of BSs is preselected based on the large-scale fading factors. By limiting the search in the subset, the complexity is reduced significantly. Although the obtained power vector with the simplified algorithm is not optimal, a performance close to the macronetwork full coordination can be achieved by carefully choosing the sizes of the pre-selected BS subset and MBS. The significant advantage is proven by simulations.